Acute Ischemic Stroke in COVID-19: Putative Mechanisms, Clinical Characteristics, and Management. (11th November 2020) - Ojo, Ademola S.; Balogun, Simon A.; Idowu, Ahmed O.
Abstract : The emergence and spread of the highly contagious novel coronavirus disease (COVID-19) have triggered the greatest public health challenge of the last century. Aside from being a primary respiratory disease, acute ischemic stroke has emerged as a complication of the disease. While current evidence shows COVID-19 could cause ischemic stroke especially in severe disease, there are similarities in the risk factors for severe COVID-19 as well as ischemic stroke, underscoring the complex relationship between these two conditions. The pandemic has created challenges for acute stroke care. Rapid assessment and time-sensitive interventions required for optimum outcomes in acute stroke care have been complicated by COVID-19 due to the need for disease transmission preventive measures. The purpose of this article is to explore the putative mechanisms of ischemic stroke in COVID-19 and the clinical characteristics of COVID-19 patients who develop ischemic stroke. In addition, we discuss the challenges of managing acute ischemic stroke in the setting of COVID-19 and review current management guidelines. We also highlighted potential areas for future research.